TEACHER’S BELIEF TOWARD THE IMPLEMENTATION OF SCIENTIFIC APPROACH IN 2013 CURRICULUM AND ITS PRACTICES ON ENGLISH CLASSROOM - Lailatus Sa'adah (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2019)
This research aims to investigate the teacher’s belief toward the implementation of scientific approach in 2013 curriculum and its practices in English classroom, how those beliefs are reflected in their classroom practices, and the factors influencing those beliefs and practices. The researcher applied the descriptive qualitative design by using the opened questionnaire as the instrument. The results of this study showed that: (1) most of teacher had already understood the concept of scientific approach; (2) there are several problems arose in the implementation of scientific approach of 2013 curriculum in English classroom or its practices; and (3) factors which influence teachers thought related to the implementation of scientific approach in English classroom are time allotment, teacher’s understanding toward their role in teaching learning process, learning media, facilities, and motivation for both teacher and student.